2013
DOI: 10.1525/jer.2013.8.5.40
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Research Ethics Capacity in the Middle East: Experience and Challenges of a Fogarty-Sponsored Training Program

Abstract: we describe the research ethics capacity needs of the countries from the Middle East region. Against this background, we relate the experience of an international training program focused on providing long-term training in research ethics to individuals from low- and middle-income countries in the Middle East area. We describe our pedagogical approach to training, program changes to address challenges faced, and accomplishments of trainees. Many former trainees developed research ethics curricula in their home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Six of these nine programs remain funded beyond 2012. This review excludes awards for North Africa or the Middle East region, which are covered in a separate paper (Silverman et al, 2013). We present key information on the nine programs in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Six of these nine programs remain funded beyond 2012. This review excludes awards for North Africa or the Middle East region, which are covered in a separate paper (Silverman et al, 2013). We present key information on the nine programs in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The utility of such programs has been documented. For example, Silverman, Edwards, Shamoo, and Matar (2013) describe the benefits of a Fogarty-sponsored and other sponsored ethics training programs in the Middle East, and Ndebele and colleagues (2014) provide a review of Fogarty-sponsored programs addressing research ethics capacity building in sub-Saharan Africa. Training programs should be tailored to the needs of the institution and its members and may range from short-term intensive one-week fundamental ethics trainings for REC members and faculty to long-term (six months to two years) training programs for a smaller number of interested REC members and faculty.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of competent committees and comprehensive standards for REC functioning in LMICs is highlighted in the literature (Adams et al, 2014; Chenneville et al, 2014; Makhoul et al, 2014; Matar & Silverman, 2013; Silverman, Edwards, Shamoo, & Matar, 2013; Silverman & Sleem, 2014; Silverman et al, 2014). Nonetheless, concerns remain.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, more than a third of the researchers did not have training in research ethics. Inadequate research ethics training was demonstrated in several studies conducted in developing countries . A survey of the faculty members at Cairo University in Egypt showed that almost half of them never attended a course in research ethics .…”
Section: Discussionmentioning
confidence: 99%